Study of ICT Integrated Challenge Based Learning on Statictical Thinking Ability (Jurusan Matematika FMIPA UNNES, 2023)
The research method used is a literature study that uses secondary data with search keywords according to the purpose. The data analysis technique consists of three stages, namely organize, synthesize, and identify. The results achieved are the formation of stages of learning ICT integrated challenge based learning model based on the literature that has been analyzed and the relationship between ICT integrated challenge based learning models on statistical thinking ability. Based on the results and discussion, it was obtained that the ICT integrated challenge based learning model can be an innovative solution to develop statistical thinking ability. Learning with an ICT integrated challenge based learning model will facilitate students to carry out activities in a series of processes that are mutually sustainable, ranging from identification, characterization, measurement, control and reducing variation activities providing opportunities for improvement in the process to be able to solve problems related to data in real word problem as it becomes characteristic of statistical thinking. The suggestion proposed is that further research is needed on the development of learning instruments and media with an ICT integrated challenge based learning model that contains indicators of statistical thinking ability and the implementation of these models in mathematics learning.